Dynamic Route Allocation for Guaranteed Data Delivery in Mobile Ad Hoc Networks using DPRP & VDVH (International Journal of Engineering and Computer Science, 2015)
-Mobile Ad hoc networks (MANET) carried out multi-hop communication in an environment with nofixed infrastructure, by means of mobile nodes and changing network topology. In mobile ad hoc networks(MANETs), nodes move freely and so the topology of the nodes is highly dynamic. The process of routing the datapackets to the destination is a challenging task.Provoked by this issue, this paper presents the new approach aDynamic Position Based Routing (DPRP) protocol which implemented in the distributed architecture and takesadvantage of the stateless property of geographic routing and the broadcast nature of wireless mediumdynamically.In the case of communication hole, a Virtual Destination-based Void Handling (VDVH) scheme isfurther proposed to work together with DPRP. Both theoretical analysis and simulation results show that DPRPachieves excellent performance even under high node mobility with acceptable overhead and the new voidhandling scheme also works well.